Breeding histories and selection criteria for oilseed rape in Europe and China identified by genome wide pedigree dissection - Wang, Xiaohua; Long, Yan; Wang, Nian; Zou, Jun; Ding, Guangda; Broadley, Martin R.; White, Philip J.; Yuan, Pan; Zhang, Qianwen; Luo, Ziliang; Liu, Peifa; Zhao, Hua; et al. (Nature Publishing Group, 2017)
Selection breeding has played a key role in the improvement of seed yield and quality in oilseed rape (Brassica napus L.). We genotyped Tapidor (European), Ningyou7 (Chinese) and their progenitors with the Brassica 60 K Illumina Infinium SNP array and mapped a total of 29,347 SNP markers onto the reference genome of Darmor-bzh. Identity by descent (IBD) refers to a haplotype segment of a chromosome inherited from a shared common ancestor. IBDs identified on the C subgenome were larger than those on the A subgenome within both the Tapidor and Ningyou7 pedigrees. IBD number and length were greater in the Ningyou7 pedigree than in the Tapidor pedigree. Seventy nine QTLs for flowering time, seed quality and root morphology traits were identified in the IBDs of Tapidor and Ningyou7. Many more candidate genes had been selected within the Ningyou7 pedigree than within the Tapidor pedigree. These results highlight differences in the transfer of favorable gene clusters controlling key traits during selection breeding in Europe and China.